2023
DOI: 10.1101/2023.01.23.525219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soybean and cotton spermosphere soil microbiome shows dominance of soil-borne copiotrophs

Abstract: The spermosphere is the transient, immediate zone of soil around imbibing and germinating seeds, rich in microbial activity. It represents a habitat where there is contact between seed-associated microbes and soil microbes, but is studied less compared to other plant habitats. Previous studies on spermosphere microbiology were primarily culture-based or did not sample the spermosphere soil as initially defined in space and time. Thus, the objectives of this study were to develop an efficient strategy to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…The data files and scripts used for this analysis are available on GitHub ( https://github.com/Noel-Lab-Auburn/SpermosphereMicrobiome2022 ) ( 83 ). Raw sequence reads were deposited to the sequence read archive with BioProject number PRJNA925866 .…”
Section: Methodsmentioning
confidence: 99%
“…The data files and scripts used for this analysis are available on GitHub ( https://github.com/Noel-Lab-Auburn/SpermosphereMicrobiome2022 ) ( 83 ). Raw sequence reads were deposited to the sequence read archive with BioProject number PRJNA925866 .…”
Section: Methodsmentioning
confidence: 99%
“…Co-occurrence networks were constructed to characterize the relationship between core taxa and the whole community using the NetCoMi v1.1.0 package, as previously described (Olofintila & Noel, 2023; Peschel et al ., 2021), and hub ASVs were identified as those that are significantly more connected within the network than other ASVs on the basis of centrality measures (Banerjee et al ., 2018). To construct the correlation matrix, the SpiecEasi v1.1.2 tool (Kurtz et al ., 2015) was used on nonrarefied count data as SpiecEasi performs centered log-ratio normalisation internally.…”
Section: Methodsmentioning
confidence: 99%
“…Like other habitats (i.e. rhizosphere and phyllosphere), the nature and quantities of exudates is an important driver of microbial community composition (10). This is perhaps even more striking within the spermosphere since the plant defense responses appear to be not induced during germination (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The former is based on the rapid and efficient use of resources, a strategy used by copiotroph (14). High relative abundance of copiotrophic bacterial taxa have been reported in seedlings (15,16) and spermospheres (10) of different plant species. These observations suggested that this life history strategy is important for seed to seedling transmission.…”
Section: Introductionmentioning
confidence: 99%